Bridging nature and urbanity through green roof resilience framework (GRF): A thematic review - Alishba Saqib; M Sana Ullah Khan; Irfan Ahmad Rana (Nature-Based Solutions, 2024)
The impacts of climate change pose a critical research challenge for sustainability. Despite growing awareness of green roofs as nature-based solutions, a significant gap exists in understanding their role in urban resilience. The research reviews thematic perspectives of green roofs in improving urban resilience. The paper used the PRISMA framework to systematically review the literature on green roofs and climate change, utilizing the keywords ''green roof*” and climate change'' in the Web of Science database. Bibliometric and thematic analysis is used to observe research trends from 123 publications that meet inclusion criteria, which include selected keywords, language, and publication type. Recurrent themes included urban heat islands, stormwater runoff, thermal comfort, biodiversity conservation, carbon footprint reduction, urban agriculture, and human well-being. The study proposes the Green Roof Resilience Framework (GRF), which combines these ideas into a systematic method for enhancing urban resilience. The research advocates for mainstreaming green roofs into adaptation planning, envisioning the creation of sustainable and resilient societies.